2004
DOI: 10.1093/jnci/djh192
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Antiretroviral Therapy and Cervical Squamous Intraepithelial Lesions in Human Immunodeficiency Virus-Positive Women

Abstract: HAART use was associated with increased regression of SIL among HIV-infected women, and among women who used HAART, increased CD4+ T-cell counts were associated with a greater likelihood of regression. However, the majority of cervical lesions among HIV-infected women, even among individuals who used HAART, did not regress to normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 29 publications
0
70
0
2
Order By: Relevance
“…Thus from the present study, it can be said that prevalence of lower genital tract infections is more common in HIVpositive women [12], whereas it can very well be concluded that HIV-positive women who were on HAART showed an increased clearance of HPV infections because of increased immune function.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Thus from the present study, it can be said that prevalence of lower genital tract infections is more common in HIVpositive women [12], whereas it can very well be concluded that HIV-positive women who were on HAART showed an increased clearance of HPV infections because of increased immune function.…”
Section: Resultsmentioning
confidence: 51%
“…In Ahdeich Grant et al [11,12], Hanskin's [13], Firnhasen [14], and Heard et al studies [15,16], they all said that low CD4 counts and increased HIV viral loads have an independent association with the incidence of delayed clearance of HPV infections as well as with the risk of progression of SIL (squamous intra-epithelial lesions).…”
Section: Cd4 Count and Its Association With The Colposcopic Findings mentioning
confidence: 99%
“…Women who used antiretroviral therapy have been found to present higher rates of IEL regression (Minkoff et al 2001, Ahdieh-Grant et al 2004). This seems plausible, since antiretroviral therapy reverses immunodeficiency, thereby increasing the number of TCD4 cells (Heard et al 1998) and reducing the viral load (Wagner et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, local Treg and pDC immunotherapy might be useful as adjuvants to reduce the risk of recurrent cervical neoplasia, especially in HIVpositive and other high risk populations. It is also possible that the relation of Tregs and pDCs with oncHPV persistence may play a role in the beneficial effects of HAART in reducing oncHPV persistence observed in prior studies (1,2,12). Larger and more comprehensive studies are therefore warranted to expand upon the current observations, and better understand the effects of pDCs and Tregs on HPV natural history.…”
mentioning
confidence: 86%